Prepare for the unanticipated: Portfolios of coping strategies of rural households facing diverse shocks. (December 2020) - Paumgarten, Fiona; Locatelli, Bruno; Witkowski, Ed T.F.; Vogel, Coleen
Abstract: Rural households have established various informal strategies to cope with unanticipated shocks. These existing coping strategies are receiving renewed interest, particularly in the context of climate change and in terms of the role they do, and can play, in enhancing households' adaptive capacity. An improved understanding of these strategies, and the factors that influence their application, may support the design of locally relevant adaptation strategies. We explored the nature and prevalence of unanticipated shocks, including natural hazards, experienced by households in two villages in Venda, South Africa, with the villages selected, in part, because of notable differences in precipitation. We considered the influence of shock type, and household- and location-specific characteristics, on the use of various household-level coping strategies. We report on semi-structured interviews, administered to 170 randomly selected households, and a participatory rural appraisal. Almost 90% of households reported the experience of at least one unanticipated shock over a prescribed 5-year period, with natural hazards reported by 42%. The type of shock experienced and various household-level characteristics, such as households' access to human and financial capital, influences households' coping response. Households' access to natural and social capital allowed for the protection of ex-ante coping options. Overall, our findings indicate that when possible, households actively manage their coping strategy portfolio, both in response to the shock experienced and in anticipation of future shocks. Generally, households' informal, ex-post coping options appear to be insufficiently robust for the covariate nature of natural hazards, suggesting the need for interventions that support households' existing coping portfolio. Highlights: Households apply different coping strategies depending on the shocks they face. Savings help households face natural hazards but risk being depleted by frequent hazards. Forest products were rarely used to cope with natural hazards, suggesting limitations. Natural and social capital allows for the protection of households' assets and savings. Households' access to human and financial capital affects their coping choices.